Ecologia do forrageiro e quantificação de mercúrio no atobá-pardo (Sula leucogaster) (BODDAERT, 1783) em dois arquipélagos brasileiros - Benemann, Victória Renata Fontoura (Universidade do Vale do Rio dos Sinos, 2024)
The Optimal Foraging Theory predicts that a predator adjusts its foraging strategies to maximize energy gain, spending the least amount of energy possible to meet its energy demands. Foraging efficiency is a metric used to measure the final energy balance resulting from an individual's foraging activities, where the energy gain obtained by prey consumption should be greater than the energy cost of searching, capturing and ingesting it. The brown booby (Sula leucogaster) is a seabird of the Sulidae family, widely distributed in tropical and subtropical oceans both in coastal and pelagic zones and is characterized by exhibiting a high trophic plasticity. The main goal of this thesis is to investigate the foraging behavior and efficiency of brown boobies in two populations of the species, comparing the environmental conditions and the anthropic influence in each one. The specific goals are to (1) determine the foraging areas in the Moleques do Sul archipelago (MS) and investigate how oceanographic variables and the distribution of trawling fleets influence the foraging habitat use, (2) test intersexual differences in foraging behavior, (3) compare the prey species composition and nutritional quality of brown boobies diet between MS and São Pedro and São Paulo (SPSP) archipelagos, (4) compare foraging efficiency between the two archipelagos, and (5) determine and compare mercury concentration in feathers of juveniles and adults from the two archipelagos. Breeding adults (n = 39) were tracked for three days with biologgers programmed to collect geographic coordinates, acceleration, and depth data during foraging trips in both archipelagos. Of these 39 individuals tracked, 26 had their diet samples collected through spontaneous regurgitation to analyze diet and nutritional composition. To analyze mercury concentration, ventral feathers were collected from 58 individuals: 21 in MS and 37 in SPSP. No significant influence of trawling fleets spatial distribution was found on the choice for foraging areas in MS during the studied period. A significant difference was observed in protein and lipid contents, but not in energy density between the prey of the two archipelagos. Brown boobies from MS performed trips farther from the breeding colony and dived deeper, which resulted in higher energy expenditure than in SPSP. The foraging efficiency of brown boobies was higher in SPSP than in MS, probably due to the greater availability of prey in this archipelago. Regarding mercury contamination, no significant differences were observed concerning sex and age, but there were differences between the archipelagos, where individuals from MS showed higher concentrations. This thesis presents new information on the foraging behavior and mercury contamination of the brown booby in the studied archipelagos, especially for the MS population, which represents the southern limit of the species distribution in the Atlantic Ocean and is still poorly studied.
Keywords: Plasticidade trófica; Ecologia do movimento; Sulidae; Estratégia de forrageio; Pesca de arrasto; Trophic plasticity; Movement ecology; Foraging strategy; Trawling; ACCNPQ::Ciências Biológicas::Biologia Geral